Educational inequalities in dementia-related mortality using a multiple cause of death approach and their contribution to life expectancy differences in Spain - Jeroen J. A. Spijker; Júlia Almeida Calazans; Sergi Trias-Llimós; Elisenda Renteria; Gabriele Doblhammer (Scientific Reports)
Abstract We examine dementia-related mortality in Spain from 2016 to 2021, focusing on its comorbidities and educational inequalities in life expectancy at age 60. Using a multiple cause of death (MCOD) approach, we assess how dementia-related mortality varies by education level and how these differences contribute to disparities in longevity. We used mortality data from the Spanish National Statistics Institute (INE) by level of education from 2016 to 2021 to analyse mortality from dementia-related diseases (ICD-10 codes: F01-F03, G30-G31) both as underlying cause of death (UCOD) and as MCOD (irrespective of their position within the death certificate). We estimated age-standardized mortality rates and used life tables and demographic decomposition techniques to assess the impact of dementia-related diseases on educational differences in life expectancy at age 60. Results showed that in 2016-21 MCOD dementia-related deaths accounted for 17% of all deaths occurring after the age of 60 (men: 11%; women 21%). The higher MCOD dementia-related mortality experienced by the lower educated group contributed 0.13 years (8.4%) to the total life expectancy gap at age 60 between the low and high education groups for men, and 0.26 years (22.7%) for women. Educational gradients in dementia-related mortality in Spain highlight the importance of disentangling risk factors from a socioeconomic perspective. Moreover, the MCOD approach provides a more realistic estimate of the impact of dementia-related diseases on life expectancy, bringing insights into the burden of ageing-related diseases.